Arteriovenous Access: Infection, Neuropathy, and Other Complications. Issue 1 (26th September 2016) - MacRae, Jennifer M.; Dipchand, Christine; Oliver, Matthew; Moist, Louise; Yilmaz, Serdar; Lok, Charmaine; Leung, Kelvin; Clark, Edward; Hiremath, Swapnil; Kappel, Joanne; Kiaii, Mercedeh; Luscombe, Rick; et al.
Complications of vascular access lead to morbidity and may reduce quality of life. In this module, we review both infectious and noninfectious arteriovenous access complications including neuropathy, aneurysm, and high-output access. For the challenging patients who have developed many complications and are now nearing their last vascular access, we highlight some potentially novel approaches.